Anti-cyclic citrullinated peptide (Anti-CCP) autoantibody as a useful diagnostic test for the diagnosis of rheumatoid arthritis - Dollah, Rusni (2010)
Rheumatoid factors are currently used in the diagnosis of rheumatoid arthritis and constitute one of the classification criteria proposed by the American College of Rheumatology. However, rheumatoid factor positivity shows low diagnostic specificity because it is also present in patients with other autoimmune and infectious disease and even in a proportion of normal healthy individuals. Recently, another test of interest in the diagnosis of rheumatoid arthritis is the assay for anti-cyclic citrullinated peptide (anti-CCP) antibodies. To determine the sensitivity and specificity of anti-cyclic citrullinated peptide antibodies in rheumatoid arthritis patients attending HUSM using American College of rheumatology (ACR) criteria as a gold standard and to compare the sensitivity and specificity of anti-CCP and rheumatoid factor. This was a cross sectional study which conducted from January 2008 to December 2008. The study consisted of 261 patients, 96 patients with rheumatoid arthritis (cases) and 165 patients with arthritis or arthralgia but not fulfilled ACR criteria for rheumatoid arthritis (controls). Serum from each subject was tested for anti-CCP antibodies and IgG RF by enzyme linked immunosorbent assay (ELISA). However, antibodies testing unable to do to 12 blood sample from the control group due to blood lysis. Sensitivity and specificity of the test were evaluated using the clinical diagnosis as the gold standard. The sensitivity of anti-CCP was 69.8% with 94.8% of specificity. For rheumatoid factor the sensitivity was 84.5% and specificity was 74.5%. The positive predictive value for anti-CCP was 89.3% whereas for rheumatoid factor was 67.5%. The sensitivity and specificity of anti-CCP antibodies and rheumatoid factor was significantly different with p-value of< 0.001. Anti-CCP antibody has a higher diagnostic specificity and positive predictive value than rheumatoid factor, however sensitivity was lower than rheumatoid factor.